Predicted alteration of surface activity as a consequence of climate change. Issue 11 (16th September 2020) - Gade, Meaghan R.; Connette, Grant M.; Crawford, John A.; Hocking, Daniel J.; Maerz, John C.; Milanovich, Joseph R.; Peterman, William E.
Abstract: Wildlife are faced with numerous threats to survival, none more pressing than that of climate change. Understanding how species will respond behaviorally, physiologically, and demographically to a changing climate is a cornerstone of many contemporary ecological studies, especially for organisms, such as amphibians, whose persistence is closely tied to abiotic conditions. Activity is a useful parameter for understanding the effects of climate change because activity is directly linked to fitness as it dictates foraging times, energy budgets, and mating opportunities. However, activity can be challenging to measure directly, especially for secretive organisms like plethodontid salamanders, which only become surface active when conditions are cool and moist because of their anatomical and physiological restrictions. We estimated abiotic predictors of surface activity for the seven species of the Plethodon jordani complex. Five independent data sets collected from 2004 to 2017 were used to determine the parameters driving salamander surface activity in the present day, which were then used to predict potential activity changes over the next 80 yrs. Average active seasonal temperature and vapor pressure deficit were the strongest predictors of salamander surface activity and, without physiological or behavioral modifications, salamanders were predicted to exhibit a higher probability of surface activity during peak active season under future climate conditions. Temperatures during the active season likely do not exceed salamander thermal maxima to cause activity suppression and, until physiological limits are reached, future conditions may continue to increase activity. Our model is the first comprehensive field‐based study to assess current and future surface activity probability. Our study provides insights into how a key behavior driving fitness may be affected by climate change.